Review of the wolf spider genus Acantholycosa Dahl, 1908 from China (Araneae, Lycosidae) - Xiang-Yun Zhang; Zhi-Sheng Zhang; Lu-Yu Wang (ZooKeys)
The genus Acantholycosa Dahl, 1908 from China is reviewed, including five species: A. aborigenica Zyuzin & Marusik, 1988, A. lignaria (Clerck, 1757), A. sterneri (Marusik, 1993), A. zang sp. nov. (♂♀) and A. zhangi sp. nov. (♂♀). Acantholycosa aborigenica and A. sterneri are recorded from China for the first time. Detailed descriptions are presented, along with photos of the habitus and copulatory organs, and a distribution map.